The power of penguins: Where tourists travel to see penguins in the wild - Wagner, Eric L.; Garcia Borboroglu, Jorge Pablo; Boersma, P. Dee (Ocean & Coastal Management)
Penguins are popular tourist attractions, but where do people go to see them in the wild? Consulting a wide range of sources, we identified 295 breeding colonies and sites that are advertised as places to visit penguins. Antarctica had the greatest number of sites (n = 123), and Namibia the fewest (n = 1). Population estimates for the number of breeding pairs were available for over 90% of sites, but both the recentness and reliability of the estimates were highly variable. The number of annual visitors was tracked at only 50% of sites. The number of breeding pairs a destination had did not predict its visitors per year. The closer a site was to a city with an airport, the more visitors it received. Excluding sites in Antarctica and the Galápagos, where visits are more tightly regulated and more boat-based, less than half of sites had specific management plans. Entrance fees ranged from zero to several thousand U.S. dollars, but fees rarely were used to support conservation or research. In sum, penguin-related tourism operates in a black box, with substantial information gaps. Tourism to penguin colonies can be sustainable, but this requires 1) regulations and enforcement to keep penguins safe from excessive disturbance; and 2) funds to benefit the penguins, their ocean and coastal habitats, research, and the local community. Transparency in the number of visitors and how the revenue their visits generate is used is essential to assess the sustainability of tourism at any colony. Fil: Wagner, Eric L. University of Washington; Estados Unidos Fil: Garcia Borboroglu, Jorge Pablo. Global Penguin Society; Argentina. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - Centro Nacional Patagónico. Centro para el Estudio de Sistemas Marinos; Argentina Fil: Boersma, P. Dee. Global Penguin Society; Argentina. Wildlife Conservation Society; Estados Unidos. University of Washington; Estados Unidos